Black or right: anti/racist campus rhetorics - Maraj, Louis M., author; Utah State University Press, publisher (Colorado State University. Libraries, 2020)
Exploring notions of Blackness in white institutional-particularly educational-spaces. Theorizing how in the age of #BlackLivesMatter, Black identity operates with/against neoliberal ideas of difference. Centering Blackness in frameworks for antiracist agency through interdisciplinary Black feminist lenses and asks how those racially signifying 'diversity' in higher education (and beyond) create meaning.--Provided by publisher.
Introduction: "It ain't that deep": deep rhetorical ecologies and para/ontological Blackness -- "Are you Black, though?": Black autoethnography and racing the graduate student/instructor -- Composing Black matter/s: hashtagging as marginalized literacy -- "Alls my life I had to fight": shaping #BlackLivesMatter through literacy events -- The politics of belonging...: when "becoming a victim of any crime is no one's fault" -- Conclusion: de ting about Blackness: (a meditation).
Keywords: Blacks -- Race identity -- United States; Rhetoric -- Study and teaching; Cultural pluralism; Hashtags (Metadata); Anti-racism; Black lives matter movement; United States -- Race relations -- 21st century